The Dırect Impact Of Corruptıon On Foreıgn Dırect Investment In Brıc Countrıes - Yin Li Tun; Dharshinie Nalliah (Universitas Internasional Batam, 2021)
This paper investigates the direct impact of corruption to foreign direct investment in BRIC countries, namely Brazil, Russia, India and China, which dates from 1997 to 2019. The estimation method used in this study is Pooled Ordinary Least Square (POLS) method. The estimation of this study reveals that corruption, interest rate and exchange rate have a negative relationship toward foreign direct investment whereas gross domestic product and trade to openness has a positive relationship with foreign direct investment. Moreover, exchange rate and trade to openness is significant to foreign direct investment and corruption, interest rate and gross domestic product is not significant toward foreign direct investment. The insignificant result on corruption to foreign direct investment might hints the researcher where further testing using more advance method is required to obtain accurate and robust result.